Pendidikan Multikultural Sebagai Upaya Memperkuat Kerukunan Antar Etnis Di Sekolah Dasar - Nahrul Hayat Rifani; Fitri Fitri; Musliadi Musliadi (Prodi PGSD Unsultra, 2024)
This study aims to analyze the role of multicultural education in strengthening inter-ethnic harmony at SD Negeri 102 Kendari. Multicultural education has an important role in building an understanding of cultural diversity, fostering an attitude of mutual respect, and reducing the potential for conflict in the elementary school environment. This study uses a quantitative method with a survey approach involving students and teachers as respondents. The instrument used is a questionnaire that measures the level of students' understanding of multicultural values, attitudes of tolerance, and social interaction in the school environment. The results of the study indicate that the implementation of multicultural education at SD Negeri 102 Kendari contributes significantly to increasing harmony between students from various ethnic backgrounds. Learning that integrates multicultural principles has proven effective in creating an inclusive and conducive learning environment for the creation of harmony. This study recommends strengthening the implementation of multicultural education in the elementary school curriculum as an effort to strengthen unity in diversity from an early age.